Character Education in Indonesia: Do Integrated Islamic Schools Outperform Public Schools? - Safitri, Islamiani; Andriyanti, Erna; Ansyari, Rizli; Harahap, Risma Delima; Pasaribu, Laili Habibah; Harahap, Rofiqoh Hasan; Istiqlal, Muhammad (Journal of Education Culture and Society, 2025)
Aim. Many parents in Indonesia currently believe that character education in Integrated Islamic Schools is superior to that in public schools. To support this belief, it is necessary to analyse students’ character and compare the implementation of character education in these schools. Methods. This study used an explanatory sequential mixed methods approach and involved 1,024 students. In the study, the quantitative stage used the survey method, and the qualitative stage used the narrative method. The research analysed the character of discipline, creativity, independence, and caring. Questionnaires in character scales collected from the participants were analysed using Multivariate Analysis of Variance (MANOVA) statistics. Document studies and interviews with vice principals were conducted to gain insight into implementing the character education programme at the school. The data obtained from this study were then analysed and integrated for further interpretation. Results. The study results showed a significant difference in the character values of discipline, creativity, and caring between public and Integrated Islamic school students. However, the independence value was higher in Integrated Islamic school students than in public school students. The difference occurs because the programmes that support character independence in integrated Islamic schools are more varied. The implementation of character education in public schools prioritises discipline, making students excel in this trait, even though the results of this study show only a minimal difference. Conclusion. This study implies that parents who want their children to be more independent should go to Integrated Islamic schools, while to strengthen the character of discipline, parents can send their children to public schools. It is important to note that this study only focuses on character values: discipline, independence, creativity, and caring.